Google Classroom Based Instruction In Teaching English - Sabrina Retnasari Iswahyudi; Syarifuddin Dollah; Murni Mahmud (Har Press Indonesia, 2021)
The use of Google Classroom in English Language Teaching is common nowadays. This research aims at finding out the implementation on Google Classrooms based instruction in teaching English in the EFL classroom, teachers’ perception on Google Classroom based instruction, and the impacts of Google Classroom based instruction on students’ learning achievement. This research is a case study using single-case study type. This research was conducted at Junior High School of 1 Pallangga Gowa. The subject of the research was two English teachers and selected using purposive sampling technique. This research found that teachers used Google Classroom for conducting online English teaching and learning at SMP 1 Pallangga Gowa. Teachers used Google Classroom as alternative platform to maximize the learning and obtained an effective online learning. In addition, it used to reduce the cost for online learning. Teachers had a positive perception on Google Classroom. Google Classroom is considered more practical and inexpensive for conducting online learning. Google Classroom has an impact on students’ achievement. However, it cannot be ascertained that the assignments submitted by students are actually done by them or not.